Application of homogenization to evaluation of effective moduli of linear elastic trabecular bone with plate-like structure - Gałka, A.; Telega, J.J.; Tokarzewski, S. (Archives of Mechanics, 1999)
Cancellous bone with plate-like architecture is modelled as an elastic cellular solid with regular microstructure. General formulae for the effective moduli are derived. Specific examples concern plate-like cancellous bone with isotropic trabeculae.